2020
DOI: 10.1177/0263775820911942
|View full text |Cite
|
Sign up to set email alerts
|

Storing value: The infrastructural ecologies of commodity storage

Abstract: As Marx pointed out in the second volume of Capital, storage is a critical moment in the circulation of capital. Yet, despite the resurgent interest in the political economy of circulation, logistics, and infrastructures, commodity storage remains under-examined in critical human geography. This paper examines the “hidden abode” of storage by tracing attempts to control moisture and realize value in two different commodity chains: Newfoundland saltfish and American grain in the late-19th- and 20th centuries. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 61 publications
1
25
0
2
Order By: Relevance
“…The latter is a condition where a suite of entities, potentials and forces animate, and have bearings upon, the circulation, assembly and contestations of infrastructure. Yet, barring a small and nascent body of work attentive to circulation (Amin and Thrift, 2017; Banoub and Martin, 2020; Mitchell, 2002), sensing and mediation (Gabrys, 2014; Parks, 2017), and multispecies assemblages (Carse, 2012; Doherty, 2019; Wakefield and Braun, 2019), scholarship on infrastructures remain largely anthropocentric in their outlook.…”
Section: Infrastructure and Non-human Lifementioning
confidence: 99%
“…The latter is a condition where a suite of entities, potentials and forces animate, and have bearings upon, the circulation, assembly and contestations of infrastructure. Yet, barring a small and nascent body of work attentive to circulation (Amin and Thrift, 2017; Banoub and Martin, 2020; Mitchell, 2002), sensing and mediation (Gabrys, 2014; Parks, 2017), and multispecies assemblages (Carse, 2012; Doherty, 2019; Wakefield and Braun, 2019), scholarship on infrastructures remain largely anthropocentric in their outlook.…”
Section: Infrastructure and Non-human Lifementioning
confidence: 99%
“…These transfers of value, as several accounts have pointed out, become determined in terms of rent as one of the necessary forms through which the equalisation of the general rate of profit asserts itself (see Iñigo Carrera 2017; Roy 2017; Starosta 2010). After being a relatively sidelined dimension of his mature work for decades, Marx's reading of circulation (and of circuits of capital) has been garnering increasing scholarly interest in recent years (Arthur and Reuten 1998; Harvey 2013), especially within critical studies of logistics (Arboleda 2019(Arboleda , 2020aBanoub and Martin 2020;Cowen 2014;Danyluk 2018). The Marxian analytic of circulation is of particular relevance for this article insofar as it enables the analytical dissection of how property regimes both constrain and make possible the movement of the circuit in each of its three moments, which roughly coincide with the interlocking motive forces of supply chain capitalism: production, commodity circulation, and finance.…”
Section: Rent and The Circulation Of Capitalmentioning
confidence: 99%
“…land, warehouses, buildings, railways, roads, port infrastructure, etc.) (see Banoub and Martin 2020;Danyluk 2018;Gregson et al 2017). They have also revealed that the logistics revolution has led a systematic assault on labour, degrading the material conditions of frontline workers in the global economy and intensifying conflict between classes and fractions of classes.…”
Section: Rent and The Circulation Of Capitalmentioning
confidence: 99%
See 2 more Smart Citations